An Innovative Optical Sensor for the Online Monitoring and Control of Biomass Concentration in a Membrane Bioreactor System for Lactic Acid Production - Fan, Rong; Ebrahimi, Mehrdad; Quitmann, Hendrich; Aden, Matthias; Czermak, Peter (My University, 2016)
Accurate real-time process control is necessary to increase process efficiency, and optical sensors offer a competitive solution because they provide diverse system information in a noninvasive manner. We used an innovative scattered light sensor for the online monitoring of biomass during lactic acid production in a membrane bioreactor system because biomass determines productivity in this type of process. The upper limit of the measurement range in fermentation broth containing Bacillus coagulans was ~2.2 g·L?1. The specific cell growth rate (µ) during the exponential phase was calculated using data representing the linear range (cell density ? 0.5 g·L?1). The results were consistently and reproducibly more accurate than offline measurements of optical density and cell dry weight, because more data were gathered in real-time over a shorter duration. Furthermore, µmax was measured under different filtration conditions (transmembrane pressure 0.3–1.2 bar, crossflow velocity 0.5–1.5 m·s?1), showing that energy input had no significant impact on cell growth. Cell density was monitored using the sensor during filtration and was maintained at a constant level by feeding with glucose according to the fermentation kinetics. Our novel sensor is therefore suitable for integration into control strategies for continuous fermentation in membrane bioreactor systems.
Citation: Fan, R.; Ebrahimi, M.; Quitmann, H.; Aden, M.; Czermak, P. An Innovative Optical Sensor for the Online Monitoring and Control of Biomass Concentration in a Membrane Bioreactor System for Lactic Acid Production. Sensors 2016, 16, 411.
Keywords: Biomass Measurement; Online Monitoring; Optical Sensor; Lactic Acid Production; Membrane Filtration